HUBUNGAN GAYA HIDUP, STATUS GIZI DAN AKTIVITAS FISIK DENGAN TINGKAT KESEGARAN JASMANI (STUDI PADA ATLET SOFTBALL PERGURUAN TINGGI DI SEMARANG TAHUN 2017) - Elvia Raissa Vania; Siti Fatimah Pradigdo; Sri Achadi Nugraheni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The Achievement of college softball athletes in Semarang has not reached the expectation. This condition can be caused by the low level of physical fitness influenced by lifestyle, nutritional status and physical activity. The aim of this study was to analyse the correlation between lifestyle, nutritional status, physical activity and the level of physical fitness in softball athletes. This study was an explanatory research with a cross sectional design. Population were all of the softball athlete aged 17-25 years old in UNDIP, UNNES and UPGRIS. Total sampling technique was used, 43 respondents met the inclusion criteria. Data were obtained by interview using structured questionnaires and analyzed using Rank Spearman correlation test. The results showed that 20.9% of the respondents were heavy smokers and 16.3% consumed alcohol. As many as 48.8% were overweight and obese by BMI, 70.4% were classified as overweight and obese based on body fat percentage for male athletes, 31.2% were overweight and obese based on body fat percentage for female athletes. Most of the respondents (55.8%) were classified as having low physical activity level and 76.7% were classified as having poor physical fitness. There were positive correlations between Body Mass Index (BMI) (p = 0.001), male body fat percentage (p = 0.001), female body fat percentage (p = 0.001), physical activity (p = 0.001) and physical fitness level in softball athletes. There was no correlation between smoking and alcohol comsumption with physical fitness level in this study. It is recommended that athletes avoid smoking and alcohol consumption, pay attention to food intake and physical activity to maintain body weight in order to obtain optimal physical fitness.